Extensão universitária na visão de bolsistas de extensão da UFLA: subsídios para a compreensão das funções da universidade pública - Ananias, Raquel de Figueiredo (2022)
University extension, in a contemporary perspective, has the important role of articulating the university with other society sectors, promoting the knowledge construction, improvement of student education and the social reality transformation. University extension in Brazil has gone through different conceptions and practices, often surrounded by dichotomies and contradictions. Having its origins in welfare practices, it currently seeks to consolidate dialogical, educational practices aimed at meeting society's demands. However, it is clear that the extension has not been properly understood in the universities. This ends up making it difficult for students to understand it, who are often unaware or have a limited knowledge of what the extension and its practice refer to. In this sense, it was intended in this technical project to know the understanding of extension scholarship students at the Federal University of Lavras regarding university extension and systematize content on the subject considering their demands. To this end, we sought to carry out a diagnosis, through a descriptive research, using quali-quantitative data, through the semi-structured questionnaire application to extension scholarship students selected by PROEC/UFLA Public Notices nº 1/2021 and 4/2021. Diagnosis results showed that most of the extension scholarship students are unaware of the contemporary concept of university extension as well as the guidelines, extension actions and participatory methodologies. Based on these results, it was possible to plan and execute intervention actions in order to contribute to the knowledge expansion about university extension of the scholarship students. From the dialogue with the extension scholarship students and other actors involved, a booklet was prepared with the main topics related to the theme. Finally, evaluation of technical project was carried out. It is considered that the results of this work reinforce the relevance of guiding university extension in the various spaces of the university in order to contribute to a more effective performance and in line with the contemporary conception of extension, in view of the mandatory curricularization of extension. It is expected that the booklet will be a material to guide and support the extension activities of the academic community at UFLA.